Effect of Use Audio Visual Media and Motivation on Student Learning Outcomes in Arts and Culture Subjects at SMP Negeri 17 Kerinci - Yundari Afrinata; Irwan (MultiTech Publisher, 2023)
The influence of the use of audio visual media and motivation on student learning outcomes in arts and culture subjects at SMP Negeri 17 Kerinci. This research aims to find out whether there is an influence from the use of audio-visual media (X1) and motivation (X2) on learning outcomes (Y). This research approach is quantitative with quasi experimental method. Data collection techniques using observation techniques, interviews, questionnaires (questionnaires), tests and documentation. The sample in this study were 33 students in the experimental class using audio-visual media and 33 students in the control class. In this study using multiple linear regression analysis and F test and T test. This study concluded that the results of testing the t test on hypothesis 1 of 4.415 means t count > t table (4.415 > 0.355) and significance (0.000 < 0.05) then it can be concluded that there is an influence of the use of audio- visual media (X1) on learning outcomes (Y). Hypothesis 2 testing the t test of (4.906 > 0.355) and significance (0.000 < 0.05) so there is an effect of motivation (X2) on student learning outcomes (Y). Hypothesis 3 testing the t test of (2.798 > 0.355) and significance (0.000 <0.05) so there is an influence of audio-visual media (X1) and motivation (X2) simultaneously on student learning outcomes at SMP Negeri 17 Kerinci.